Darstellung, Eigenschaften und spektroskopische Untersuchungen von Dialkylgallium bzw. Dialkylindiumderivaten des N-Methylacetamids - H.-U. Schwering; J. Weidlein (CHIMIA)
The preparation and the properties of dialkylgallium and dialkylindium derivatives of N-methyl acetamid are described. The IR-, Raman- and 1H-NMR-spectra of these compounds are assigned to structures with ONC-bridged eight-membered rings.